Heat and Mass Transfer - Baehr, Hans Dieter. (Springer Berlin Heidelberg : Imprint: Springer, 2006)
This comprehensive textbook provides readers with a firm foundation in the principles of heat and mass transfer and shows them how to solve problems by applying modern methods. The basic theory is developed systematically, and the solution methods to all important problems are covered in detail. The second edition incorporates state-of-the-art findings on heat and mass transfer correlations. Therefore, this book will be useful not only to upper- and graduate-level students, but also to practicing scientists and engineers. Many worked-out examples and numerous exercises with their solutions will facilitate learning and understanding, and an appendix includes data on key properties of important substances.